ANALISIS DETERMINAN PELAKSANAAN E-GOVERNMENT DI KOTA SEMARANG (STUDI KASUS www.semarangkota.go.id) - Annisya Dwi Mardiyani; Aufarul Marom (Jurusan Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2017)
E-Government makes public and private sector interact with government easily via electronic media. The problem that arises is Semarang entered the lower categories of e-government votes in 2014 by Ranking E-Government of Indonesia (PEGI) Ministry of Communication and Information of the Republic of Indonesia. The purpose of this study is to assess the implementation of e-government in Semarang city and the factors that hinder the implementation of e-government in the Semarang city. The method used is qualitative descriptive. The results showed that the lack of regulations implementing e-government, the workload of human resources in some SKPD is too large, the difficulty of the installation of network infrastructure in the city, the financial resources of e-government Semarang financed by the budget; there are many benefits and no rejection from the public. Factors that hinder the implementation of e-government are the government support in terms of policy, human resource, and infrastructure resources. Overcoming limiting factor is the government of Semarang can formulate rules on the implementation of e-government so that Semarang has a reference in the implementation of e-government, SKPD provides a reliable employee in managing websites, installation and reparation of network done at night.